Kajian Karakteristik Iklim Mikro Dalam Pemukiman: Sebuah Pendekatan Berwawasan Lingkungan Untuk Penataan Lingkungan Binaan - M. Ratodi (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2015)
Abstract: Micro-climate assessment in settlements; an environmenta-based approach built environment structuring. Global warming has become an emerging issue in the environmental field study. The urban conditions with all their environment development and layout still consider as majorrootcause for global warming. This literature study aimsed to find explanation for The rapid development of housing and high-rise buildings considered as a factor that responsible for an alternative approach in the effort of built environment restructuring. The results showed that the increasing of 70% global temperature within 1970 untills 2004. Moreover, the density of settlement area also believed as an affecting factor for air temperature increasement. In other words, the rapid presence of built environment contributes significantly to micro-climatic conditions. To accommodate the residential rapid development then the micro-climate assessment can be use as an alternative approach in the effort of built environment restructuring which can lead environmental quality improvement especially in settlement areas and to encourage the community involvement in the effort of sustainable development implementation. Keywords: micro-climate, micro-climatic characteristics, built environment, settelements